The Eksperimental Study of Cold Form Steel Closed Box Section 32 mm x 31 x 0,3 mm Under 3 Point Flexural Loading Test - Utami, Ghina; Purnomo, Heru; Swastika, Tri Widya (Politeknik Negeri Jakarta, 2025)
Cold-formed steel materials are widely used in the construction industry. One such application is closed box cold-formed steel beams, which are commonly used as battens in ceiling structures. Cold-formed steel is produced through cold roll forming or bending processes, resulting in folds along the profile. This study aims to investigate the effects of these folds on stiffness, deflection, ductility, and failure patterns. A total of 18 specimens, with lengths of 500 mm and 1100 mm, were tested using three-point bending tests. The folds were varied in location: placed in the top area, bottom area, and the side area. Tensile coupon tests were also testing to determine the material properties of the cold-formed steel. The results show that beams with a length of 500 mm can carry greater vertical loads compared to those with a length of 1100 mm. Additionally, the displacement and rotation observed in the 500 mm beams were smaller than those in the 1100 mm beams, which more significant deflection and rotation. Beams with folds located in the top area and bottom area shower greater load-carry capacity than those with folds in the web area. The failure patterns of the 500 mm beams were dominantly characterized by excessive deformation in the bottom are due to vertical loading. Similar deformation was observed in the 1100 mm beams. This excessive deformation occurred beneath the point of vertical load application with a roller-type support. Momen capacity of the experimental test results was also compared with the theoretical calculation using the Direct Strength Method, the results showed a comparative value that was almost close, but it is better to modify the formula to the theoretical formula of the Direct Strength Method for cross-sections with folds.